OPTIMIZATION OF SLABS REINFORCEMENT DEPENDING ON THE DEGREE OF BASE COMPLIANCE - Maevska, I. V.; Blashchuk, N. V.; Ivasyshyn, O. V. (Academic journal Industrial Machine Building Civil Engineering, 2017)
In the work it was made analysis of stiffness influence of upper basis construction and compliance of basics on stress−strained state of monolithic slabs and capabilities to simplify the design scheme of slabs. Two building options were considered: the one with different design: frame and frameless, the second with homogeneous and heterogeneous bases. It is established that in frame buildings only incomplete modeling of slabs shows adequate quality and does not make significant changes in constructive solution in comparison with the full simulation. For frameless buildings ignoring rigidity of upper basis and constructions compliance structures and foundations not only leads to some excess reinforcement plates, but also to the quality discrepancy reinforcement, particularly in patchy basis.